Jerusalem, Israel/Palästina. Die Grabung auf dem Zionsberg im Südwesten der Altstadt von Jerusalem (im Bereich des historischen Anglikanisch-Preußischen Friedhofs) - Vieweger, Dieter; Palmberger, Katharina (e-Forschungsberichte des DAI, 2017)
The area in the south of Mt. Zion lies within the borders of the Protestant Cemetery. Two English pioneers, F. Bliss and A. Dickie, followed the course of the ancient city walls at the end of the 19th century by digging in subterranean tunnels and discovered that there are three walls above each other in this area. The most recently constructed one is from the first half of the 5th century. An older one with the same outline as the aforementioned is the one that Flavius Josephus refers to in Jewish Antiquities and the oldest one belongs to the Iron Age. This last wall might be a rare example of the wall that Hiskijahu built as he enlarged the city to create a protected space for the refugees from the northern Kingdom of Israel at the end of the 8th century BC. In addition to Bliss and Dickie, another excavation was begun in the same area by father B. Pixner in the 1980s. Y. Zelinger, who works for the IAA, then undertook a more focused excavation in an area near the cemetery that shows the continuation of the same city walls. His results allow a partial reconsideration of the findings in the cemetery. The GPIA started its work at this exceptional and unstudied site of ancient Jerusalem in 2015. In a first season, the old excavations were carefully cleaned and documented after more than 20 years of neglect. The work concentrated on the city walls as well as on the so-called “Essene Gate” which is also mentioned by Flavius Josephus. In 2016 the project was enlarged and three large new squares were opened. These squares are in the inside of the ancient city of Jerusalem; the aim of the project is to study the city’s settlement structures. After digging through banking structures from the Modern, Islamic and Medieval periods, the excavation has now reached the Byzantine level. Many promising loci have been documented that lead into the city extension built during the time of the influential empress Eudokia in the first half of the 5th century. The upcoming seasons are expected to reveal not only fascinating Byzantine structures but monumental Hasmonean/Herodian buildings. Since there are still three meters of cultural debris to the bedrock, also the traces of the Iron Age city can be awaited in that area. The GPIA’s Mt. Zion Excavation project offers the great and rare opportunity to research the history of Jerusalem in a huge and so far untouched area directly related to the old city walls.